Strategi Perbaikan Kinerja Operasional Melalui Analisa SWOT - Wahjoedi, Tri; Sari, Anita Kartika; Yulfajar, Amrina; Shobikin; Tenovita Sari, Fajar; Etin Puspita Sari; Purwanto (STIE Mahardhika, 2024)
This community service aims to present a SWOT analysis to provide support to the company PT SJL in facing the challenges of increasing competition in the logistics industry. This SWOT approach identifies internal strengths, weaknesses, opportunities and external threats. From this analysis, 13 recommended actions were produced which were ordered based on priority to improve operational performance. S-O (optimizing strengths to take advantage of opportunities) and W-O (overcoming weaknesses to take advantage of opportunities) strategies are the main focus. Implementation of subsequent corrective actions is carried out by considering the resources owned by PT SJL, in accordance with predetermined priorities. It provides systematic and adaptive guidance to improve a company's competitiveness in a dynamic business environment.